Prednisolone-induced cholelithiasis in a Siberian Husky Dog - Hima, K.M.; A.Janus; J.Alex; P.M.Deepa; R.L.Rathish; P.Biju Habeeb; F.A.Lali (The Indian Veterinary Journal, 2026)
A one-year-old male Siberian Husky dog affected with mixed species of Babesia gibsoni and Babesia canisvogeli infection developed cholelithiasis after prednisolone therapy. Initially, gallbladder sludge was observed on hepatic ultrasonography, which progressed into cholelith during the course of treatment. Upon discontinuation of steroid therapy and the inclusion of ursodeoxycholic acid and taurine supplements in the treatment regimen,a significant reduction in the size of the cholelithwas observed.